2001
DOI: 10.1162/089892901564261
|View full text |Cite
|
Sign up to set email alerts
|

Brain Potentials Reflect Behavioral Differences in True and False Recognition

Abstract: Abstract& People often falsely recognize nonstudied lures that are semantically similar to previously studied words. Behavioral research suggests that such false recognition is based on high semantic overlap between studied items and lures that yield a feeling of familiarity, whereas true recognition is more often associated with the recollection of details. Despite this behavioral evidence for differences between true and false recognition, research measuring brain activity (PET, fMRI, ERP) has not clearly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
101
4
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 85 publications
17
101
4
8
Order By: Relevance
“…However, items that are more familiar for a variety of reasons show earlier and/ or stronger activity than less familiar items, including in our study perceptual matching, consistent with Schloerscheidt and Rugg (2004). In addition to prior study, greater familiarity may be related to greater confidence (Woodruff et al, 2006), greater gist memory (Curran et al, 2001;Duzel et al, 1997;Goldmann et al, 2003), and greater fluency (Wolk et al, 2004(Wolk et al, , 2005. (It should also be noted that some researchers view this 300 to 500 ms modulation of activity as related to conceptual priming, rather than familiarity (Voss & Paller, 2006).…”
Section: Discussionsupporting
confidence: 66%
“…However, items that are more familiar for a variety of reasons show earlier and/ or stronger activity than less familiar items, including in our study perceptual matching, consistent with Schloerscheidt and Rugg (2004). In addition to prior study, greater familiarity may be related to greater confidence (Woodruff et al, 2006), greater gist memory (Curran et al, 2001;Duzel et al, 1997;Goldmann et al, 2003), and greater fluency (Wolk et al, 2004(Wolk et al, , 2005. (It should also be noted that some researchers view this 300 to 500 ms modulation of activity as related to conceptual priming, rather than familiarity (Voss & Paller, 2006).…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, some ERP research has suggested that late frontal ERP old/new effects are related to recollection (e.g., Allan et al, 1998;Curran et al, 2001). Relating frontal activity to both source memory (as was noted above) and recollection is consistent with Jacoby's (1991) process dissociation procedure that assumes source memory to be diagnostic of recollection (Buchner, Erdfelder, Steffens, & Martensen, 1997;Mulligan & Hirshman, 1997;Steffens, Buchner, Martensen, & Erdfelder, 2000;Yu & Bellezza, 2000).…”
supporting
confidence: 67%
“…Other recent studies specifically have tested memory for when in the past an event occurred and found similar frontal ERP effects (Tendolkar & Rugg, 1998;Trott, R. Friedman, Ritter, Fabiani, & Snodgrass, 1999). Late frontal ERP old/new effects are thought to be related to postretrieval evaluation processes (Allan et al, 1998;Curran, Schacter, Johnson, & Spinks, 2001;Johnson et al, 1996;Ranganath & Paller, 2000;Wilding, 1999;Wilding & Rugg, 1997a, 1997b, and these processes may be important for location-based memory for when an event occurred.…”
mentioning
confidence: 99%
“…Third, lists with three critical words contributed to satisfy a compelling methodological need in event-related potential (ERP) DRM research. Commonly, these studies seek to examine the similarities and differences between true and false memories (e.g., Curran, Schacter, Johnson, & Spinks, 2001). Whereas the ERPs for true memories are obtained from averaging trials for studied-item hits, the ERPs for false memories are obtained from averaging critical-word false alarm trials.…”
mentioning
confidence: 99%
“…Furthermore, the disparity between the S/N ratios found in true and false memory ERP waveforms make comparisons difficult to interpret (Luck, 2005). Alternative solutions to this problem have been proposed (Curran et al, 2001;Wiese & Daum, 2006), but they have failed to maintain the DRM associative structure in the lists (see Beato & Díez, 2011, for a discussion of this alternative). Thus, three-critical-word DRM lists, the materials employed in this study, seem to constitute adequate materials to study (1)how error-editing processes are involved in false memories, (2)how error-inflating processes have an impact on false memory, and (3)false-memory ERP waveforms.…”
mentioning
confidence: 99%